Converting the Bulk Transition Metal Dichalcogenides Crystal into Stacked Monolayers via Ethylenediamine Intercalation - Ahn, Yeojin; Lee, Gyubin; Noh, Namgyu; Lee, Chulwan; Le, Duc Duy; Kim, Sunghun; Lee, Yeonghoon; Hyun, Jounghoon; Lim, Chan Young; Cha, Jaehun; Jho, Mingi; Gim, Seonggeon; et al. (Nano Letters, 2023)
We report the synthesis of ethylenediamine-intercalated NbSe2 and Li-ethylenediamine-intercalated MoSe2 single crystals with increased interlayer distances and their electronic structures measured by means of angle-resolved photoemission spectroscopy (ARPES). X-ray diffraction patterns and transmission electron microscopy images confirm the successful intercalation and an increase in the interlayer distance. ARPES measurement reveals that intercalated NbSe2 shows an electronic structure almost identical to that of monolayer NbSe2. Intercalated MoSe2 also returns the characteristic feature of the monolayer electronic structure, a direct band gap, which generates sizable photoluminescence even in the bulk form. Our results demonstrate that the properties and phenomena of the monolayer transition metal dichalcogenides can be achieved with large-scale bulk samples by blocking the interlayer interaction through intercalation.
Keywords: Angle resolved photoemission spectroscopy; Bulk; Bulk transition; Dichalcogenides; Electronic.structure; Ethylene diamine; Interlayer distance; Transition metal dichalcogenides; Transmission electron microscopy images; X ray diffraction patterns; bulk; intercalation; monolayer; MoSe2; NbSe2; transition metal dichalcogenides